Parameters of Fibrinolysis in Peritoneal Fluid and Plasma in Different Stages of the Menstrual Cycle - Dörr, P J; Brommer, E J P; Dooijewaard, G; Vemer, H M (Thrombosis and Haemostasis, 1993)
The purpose of this study was to investigate differences in fibrinolytic activity in peritoneal fluid and plasma of women in the first and second part of the menstrual cycle. Given the classic concept of decreased fibrinolytic activity as a cause of adhesion formation, and if such differences are found, the stage of women’s menstrual cycle should be taken into consideration when scheduling a laparotomy.We measured fibrinolytic parameters in peritoneal fluid and plasma in eight women in the pre-ovulatory period and in eleven women in the post-ovulatory period of the menstrual cycle.There were no differences in t-PA-Ag, t-PA-Act, u-PA-Ag and scu-PA concentrations in peritoneal fluid between the pre- and post-ovulatory group. Nevertheless, PAI-1-Ag in peritoneal fluid was three-fold higher in the post-ovulatory phase (p <0.02). In peritoneal fluid the concentrations of both TDP and FbDP were three-fold higher at the same phase (p ≥0.05).Plasma u-PA-Ag and scu-PA concentrations were significantly lower (30%, p <0.05) in the post-ovulatory phase and also lower than plasma u-PA-Ag and scu-PA (measured with the same assay) in a group of 50 healthy individuals. No differences in t-PA and PAI concentration were found.In conclusion, the intraperitoneal fibrinolytic capacity might be impaired in the second part of the menstrual cycle, regarding the elevated levels of PAI-1-Ag, leading to an increased risk for postovulatory adhesion formation. The low plasma u-PA-Ag and scu- PA levels post-ovulatory may have clinical relevance.